Time for Children, a Study of Parents' Time Allocation - Daniel Hallberg; Anders Klevmarken (Uppsala University, Department of Economics, 2001)
Process benefit scores indicates that time with own children is preferred before all other activities, closely followed by market work. The trade-off between parents time with their own kids and market work, and its dependence on out-of-home day-care is analyzed in a simultaneous equation framework. Our empirical results suggest that parents decisions about market work and time with children are strongly interdependent. Economic incentives work primarily through decisions about market work, while the direct effects on time with kids are weak. The results suggest that a change in the mothers work hours influences less the parents time with their children than a change in the fathers work hours does. This would imply that a policy working to increase the time with own children should primarily influence the fathers work hours. We also find that parents prefer joint activities with children, and that out-of-home child-care is not chosen as a substitute for own time with kids.
urn:nbn:se:uu:diva-2238
Keywords: C50; D10; J13; J22; 330; Time-use; child-care; family economics; simultaneous equation system; three-stage least squares; process benefits; Zeitverwendung; Kinderbetreuung; Familienökonomik; Schätzung; Schweden